Carbene-catalyzed desymmetrization of 1,3-diols: access to optically enriched tertiary alkyl chlorides - Li, Bao-Sheng (2017)
The introduction of a chlorine atom to a carbon center in an enantioselective manner via conventional C–Cl bond formation is difficult. Here we report a new approach to this class of tertiary alkyl chlorides with high optical purities. Instead of forming a new C–Cl bond, our approach involves carbene-catalyzed desymmetrization of 2-chloro-1,3-diols as the key step to set up the chiral carbon center with excellent enantiomeric excess.